Humanisme Masa Depan Dalam Tradisi Konjengan: Etika Islam Dan Penguatan Solidaritas Komunal Kiai Madura - Muqoffi; Zaironi, Muhammad; Shofi (LP2M IAIN Sultan Amai Gorontalo, 2026)
This study aims to analyze the konjengan tradition of kiai in Madura as a socio-religious practice that not only represents symbolic reverence but also functions as a strategic mechanism for strengthening communal solidarity within the context of contemporary Islam. Konjengan is understood as a manifestation of future-oriented humanism because it integrates spiritual authority with lived ethical practices embedded in everyday community life. This research employs a qualitative approach through participant observation and in-depth interviews to comprehensively explore interactional patterns, symbolic meanings, and relational dynamics between kiai and community members. The analysis focuses on how the sustained presence of the kiai, contextually grounded moral guidance, and consistent social engagement cultivate collective attachment, a sense of belonging, and social trust at the community level. The findings indicate that konjengan facilitates the internalization of Islamic ethical values such as empathy, humility, social responsibility, and participatory leadership, thereby counterbalancing the rise of modern individualism. Accordingly, konjengan can be understood as an adaptive, culturally grounded model of social ethics that significantly contributes to the preservation of social cohesion and community resilience.